Social and spatial mobility and self-reported heath in older-age: linkage of the Scottish Longitudinal Study to the Scottish Mental Survey 1947 - Forrest, Lynne; Dibben, Chris; Feng, Zhiqiang; Deary, Ian; Popham, Frank (International Journal of Population Data Science, 2018)
Background There is debate within the literature as to whether social mobility inflates or constrains health inequalities. The role of geographical mobility is unknown. Objectives We were interested in exploring how spatial and social mobility might impact on health in older age using linked administrative and cohort data. Methods The Scottish Mental Survey 1947 (a 1936 birth cohort of 70,805 individuals with age 11 cognitive ability test scores) was linked to the Scottish Longitudinal Study (a semi-random sample of 5.3% of the Scottish population), and the 1939 register to obtain measures of occupation and geographical location in 1939 and 1991. We examined the movement between three geographical areas (Edinburgh, Glasgow, Other) in Scotland. Four social mobility trajectories were derived. We modelled the relationship between social and geographic mobility and likelihood of having self-reported limiting long term illness (LLTI) at age 65. Findings Those who were geographically mobile to Edinburgh had the lowest rates of self-reported LLTI and those who remained resident in the Glasgow area had the highest rates. The lowest and highest rates of LLTI were found in the socially-static at the top and bottom of the social scale respectively, with intermediate rates seen in the upwardly and downwardly mobile. However neither social nor spatial mobility were significantly associated with health in later life in the fully adjusted model when highest educational qualifications and cognitive ability were included. Being female, having higher education qualifications and being in a higher social class in childhood and adulthood reduced the likelihood of poor health at age 65. Conclusions Although both social class and geographical location were associated with the likelihood of LLTI in later life, social and spatial mobility were not, when factors such as education and cognitive ability were controlled for.